Effect of Building Height on the Seismic Behavior of Steel Framed Structures - Mourad, Omar Al (Eastern Mediterranean University EMU, 2015)
Northridge-USA and Kobe-Japan earthquakes in mid 1990s caused numerous structural damages to 3, 6 and 12 story buildings, in relation to structural design and framing type. Hence, this research was aimed at studying the effect of structural framing type and building height on seismic behavior of steel structures. Equivalent Static Analysis (ESA) were carried out using ETABS software to analyze 6, 12 and 20 story Moment Resisting Frame (MRF) and Concentric Braced Frame (CBF) buildings, with regular and irregular plan and elevations. Eurocodes 3 and 8 were used for the design of 77 different building models considering soil and earthquake parameters for Lebanon. In addition selective models of both frame types were also analyzed using Response Spectrum (RS) and Nonlinear Static Pushover Analysis (NSPA). Considering the lateral displacements obtained it was found that generally up to story 15 moment frames have more displacements than braced frames with similar structure. However, for taller structures the situation was reversed and braced frames achieved more displacements than moment frames. Introducing belts at top and middle or top story only of 20 story braced framed structure generally reduced its lateral displacement in both directions except in y-direction only up to 14 floors. Pushover analysis results showed that moment framed 6 and 12 story regular buildings performed better than similar braced frame ones, and the case was vice versa for 20 story regular buildings. Keywords: Earthquake, Moment Resisting Frame, Concentric Braced Frame, Irregularity, Displacement, Height Effect, Equivalent Static, Response Spectrum, Nonlinear Static Pushover.

ÖZ: Çelik karkas yapıların birçok avantajları vardır. Bunlardan birisi depreme dayanıklılık için gerekli olan sünekliktir. 1990 yılı ortalarında meydana gelen Northridge-ABD ve Kobe-Japonya depremleri 3, 6 ve 12 katlı yapılarda bir dizi yapısal tasarım ve taşıyıcı çerçeve çeşidi alakalı zararlara neden olmuştur. Bu araştırma yapısal çerçeve çeşidinin ve bina yüksekliğinin çelik yapıların depremsel davranışına etkilerini araştırmayı amaçlamıştır. ETABS yazılımı kullanılarak 6, 12 ve 20 katlı, düzenli ve düzensiz plan ve görünüşe sahip, rijit ve çarpraz çerçeveli binalar Eşdeğer Statik yöntemle analiz edilmişlerdir. Çelik ve deprem tasarım standardları, Eurocode 3 ve 8, Lübnan deprem ve zemin parametreleri kullanılarak 77 farklı bina tasarımı yapılmıştır. İlaveten her iki çerçeve tasarımlarından seçilmiş modeller davranış spektrumu ve doğrusal olmayan statik itme yöntemleriyle analiz edilmişlerdir. Analiz sonuçlarında elde edilen veriler 15 kata kadar olan yüksekliklerde ayni tip binalarda rijit çerçeve binaların çarprazlı binalardan daha fazla yatay yer değiştirmeye maruz kaldığını göstermiştir. Diğer yandan 15 kat sonrası yüksekliklerde durumun tam ters olduğu not edildi. 20 katlı çarprazlı binaların en üst ve orta veya sadece en üst katlarına makas tipi kemer yerleştirildi. Binanın yatay yer değiştirmesi, her iki yönde, tüm katlarda rijit çerçeve binadan daha az olurken y yönünde azalma sadece 14 üncü kata kadar oldu. Doğrusal olmayan statik itme analiz sonuçları 6 ve 12 kat düzenli rijit çerçeve yapıların çapraz çerçeveli yapılardan daha iyi performansı olduğunu göstermiştir. 20 kat düzenli yapılarda ise durum tam tersidir. Keywords: Deprem, Rijit Çerçeve, Merkezi Çarpraz Çerçeve, Düzensizlik, Yer değiştirme, Yütkseklik Etkisi, Eşdeğer Statik, Davranış Spektrum, Doğrusal Olmayan Statik İtme
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2015. Supervisor: Assist. Prof. Dr. Mürüde Çelikağ.
Keywords: Civil Engineering Department; Building; Iron and steelxSteel; Structural; Structural stability; Earthquake; Moment Resisting Frame; Concentric Braced Frame; Irregularity; Displacement; Height Effect; Equivalent Static; Response Spectrum; Nonlinear Static Pushover